Waste management through biotechnological approaches - SARIKA CHATURVEDI (International Journal of Pharma and Bio Sciences, 2018)
Solid waste manegment system components are required to handle all non hazardous solid waste generated in different cities. groundwater having chlorinated ethanes, producing activated sludge/compost. Biopilling, combined composting and land farming, help natural degradation of pesticides. Rubber, in solid wastes, is non degradable/non-recyclable due to synthetic polymers/ black carbon, is devulcanized by sulfur reducing actinobacteria and Recinicium bicolour removing toxic components. Therefore the solid waste manegement of hazardous wastes is to reduce the wastes, proper transport of hazardous wastes, treatment and recovery of hazardous wastes and final disposal of the hazardous wastes. Solid waste management approaches for collection, transportation, disposal and reduction, reuse, recycling, resource recovery. This technique provides a further insight of feasibility and aids of adopting segregation at source and delegation to provide better future. This research are important to establish independent and autonomous Authority to deal with solid waste management, formalisation of the solid waste sector, legislation of the law, provision of public awareness on solid waste management etc.